The Effect of Price Perception and Product Quality on Customer Satisfaction Level at TikTok Shop in 2025 - Maefa Eka; Muhamad Nurman; Esthi Adityarini (Danadyaksa: Post Modern Economy Journal, 2026)
The growth of e-commerce in Indonesia has made TikTok Shop one of the fastest-growing social commerce platforms, with the advantage of integrating entertainment content and buying and selling transactions in one application. Although various studies have examined the factors that influence customer satisfaction, most still focus on conventional marketplaces such as Shopee and Tokopedia, resulting in a literature gap regarding the dynamics of customer satisfaction on social commerce-based platforms. This study aims to analyze the influence of price perception and product quality on TikTok Shop customer satisfaction in 2025. A quantitative method with a purposive sampling technique was applied to 125 respondents who were active TikTok Shop users and analyzed using SPSS 25 through t-test and F-test. The results showed that price perception (t=5.290) and product quality (t=7.069) each had a positive and significant effect on customer satisfaction, and both simultaneously had a significant effect (F=104.352; sig. 0.000 <0.05). This study also provides an overview of the importance of pricing perception strategies and improving product quality in building customer satisfaction on social commerce platforms. The research findings are expected to serve as a reference for digital business actors in understanding customer behavior on TikTok Shop, which has different characteristics compared to conventional marketplaces.